2010
DOI: 10.1016/j.tet.2010.10.027
|View full text |Cite
|
Sign up to set email alerts
|

The selective mono and difunctionalization of carbocyclic cleft molecules with pyridyl groups and X-ray crystallographic analysis

Abstract: Citation: JILKA, P. ... et al, 2010. The selective mono and difunctionalization of carbocyclic cleft molecules with pyridyl groups and X-ray crystallographic analysis. Tetrahedron, 66 (48) --- IntroductionMolecular recognition relies on the ability to design and synthesize appropriate substrates with predictable geometries and binding sites. 1 Towards this end Tröger's base 2 1 has been used to great effect by a number groups within the context of molecular recognition because it contains a rigid predictable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…To improve on our reported low yield synthesis of compound 3 , , we initially attempted the synthesis following the procedure reported by Jilka et al where galeterone ( 1 ) in THF was treated with sodium hydride (NaH) at 0 °C and stirred at room temperature for 10 min followed by addition of 4-(bromomethyl)­pyridine hydrobromide solution [ 14 ; THF/DMF (1:1), TEA]. The product was isolated in low yields of 24% although it was 2-fold higher than our previously reported 12% yield. , In an effort to improve the product yield, DMF and DMSO were investigated as alternative reaction solvents to THF/DMF mixture, as well as addition of phase transfer catalyst (tetrabutylmmonium iodide), but insignificant product formation improvement was observed by TLC analysis and isolated product yields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve on our reported low yield synthesis of compound 3 , , we initially attempted the synthesis following the procedure reported by Jilka et al where galeterone ( 1 ) in THF was treated with sodium hydride (NaH) at 0 °C and stirred at room temperature for 10 min followed by addition of 4-(bromomethyl)­pyridine hydrobromide solution [ 14 ; THF/DMF (1:1), TEA]. The product was isolated in low yields of 24% although it was 2-fold higher than our previously reported 12% yield. , In an effort to improve the product yield, DMF and DMSO were investigated as alternative reaction solvents to THF/DMF mixture, as well as addition of phase transfer catalyst (tetrabutylmmonium iodide), but insignificant product formation improvement was observed by TLC analysis and isolated product yields.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of Galeterone 3β-Pyridine Methoxylate (3). To improve on our reported low yield synthesis of compound 3, 13,14 we initially attempted the synthesis following the procedure reported by Jilka et al 33 where galeterone (1) in THF was treated with sodium hydride (NaH) at 0 °C and stirred at room temperature for 10 min followed by addition of 4-(bromomethyl)pyridine hydrobromide solution [14; THF/ DMF (1:1), TEA]. The product was isolated in low yields of 24% although it was 2-fold higher than our previously reported 12% yield.…”
Section: Organic Process Research and Developmentmentioning
confidence: 99%
“…5 Consequently, taking 3a (1 equiv) with phenylboronic acid 5 (6 equiv) in CH 2 Cl 2 , we found that the boronic acid rapidly solubilised to give a homogenous reaction mixture (Scheme 3). Upon removal of the solvent the 1 H and 13 C NMR spectra of the crude white solid showed the formation of one discrete product which was assigned to 3a.6 2 .…”
Section: A R T I C L E I N F O Abstractmentioning
confidence: 98%
“…To date, the only functionalization of these hydroxyl groups has been by esterification and alkylation; 1b,4 for example, we successfully demonstrated that the diol could be selectively transformed into the mono-and dipyridyl analogues, with the potential to interact with transition metals. 5 This type of interaction with transition metals is typical for pyridyl ligands of this kind, as demonstrated by Harding and co-workers who exploited such binding for the self-assembly of [2+2]-macrocycles. 3d However, we perceived an opportunity to use the pyridyl groups attached to these hydroxyl groups, in the selfassembly of boroxines.…”
mentioning
confidence: 90%
“…We have previously emphasized the practicality of 1 by appending the hydroxyl groups with pyridyl functionality, as well as highlighting the self-assembly of these pyridyl adducts with phenylboronic acid to yield bis-boroxine substrates, with the 4-pyridyl analogue being fully characterized by single crystal X-ray analysis emphasizing the chiral space. 14,15 The capacity to be able to confidently predict crystal packing to facilitate the design of new solids with sought-after physical properties has been central to the evolution of crystal engineering. 16−18 Furthermore, the ability to control secondary and tertiary structure within crystal packing has enormous potential in the development of new functional materials and devices.…”
Section: ■ Introductionmentioning
confidence: 99%